Assessing resilience of cities to hydrometeorological hazards - Bahena-Ayala, Rabindranath; ArreguÃn-Cortés, Felipe Ignacio; Cervantes-Jaimes, Claudia Elizabeth (Tecnología y ciencias del agua, 2021)
Currently, cities, productive areas and the environment are more at risk of natural or anthropogenic hazards than ever before, causing human and economic losses. In cities, hydrometeorological events have the greatest socioeconomic impact according to the United Nations, which is further exacerbated by the fact that some cities do not have the appropriate mechanisms to minimize the impacts of these phenomena. This is why it is necessary to make them safer and more dynamic so that they might have the capacity to constantly adapt to changes. To address this vulnerability issue present in cities, the concept of urban resilience has been created. It is a tool to aid public officials’ decision making process when choosing government works to be invested in from among many different structural and non-structural strengthening options for resilience.Â Before developing strategies within government agendas, however, it is necessary to identify a city’s strengths and weaknesses in order to know it’s resilience level. This paper proposes a methodology to assess the resilience level of a city to hydrometeorological hazards, called the City Resilience Index (CRI), that is based on two assessment tools: one quantitative, called the Technical Resilience Index and the other, which is called the Technical Profile of Resilience, is a qualitative analysis of the characteristics of the city. For this analysis the city of Cuernavaca, Mexico, was selected as a case study. Index results were generated from the City Resilience Index (CRI) computer program, created expressly for the application of this methodology, which gave a 45.52 % resilience rating to the city of Cuernavaca, a medium-range level of resilience.